2024
DOI: 10.1186/s12889-024-18115-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of the blood levels of specific volatile organic compounds with nonfatal cardio-cerebrovascular events in US adults

Li Jing,
Tiancong Chen,
Zhiyong Yang
et al.

Abstract: Background Cardio-cerebrovascular diseases constitute a major global public health burden. Volatile organic compounds (VOCs) exposure has become progressively severe, endangering human health and becoming one of the main concerns in environmental pollution. The associations of VOCs exposure with nonfatal cardio-cerebrovascular events have not been identified in observational study with a large sample size, so we aim to examine the association in US adult population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Akkoç et al found that post-stroke patients experienced urinary urgency in about two-thirds of patients at 6-month follow-up ( 32 ). In a recent study of U.S. adults, a positive correlation was found between exposure to VOCs and cardio-cerebrovascular events, including benzene, m-/p-xylene, o-xylene, and ethylbenzene ( 33 ). In addition, a study of 2011–2020 National Health Survey data found that exposure to VOCs may increase the risk of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Akkoç et al found that post-stroke patients experienced urinary urgency in about two-thirds of patients at 6-month follow-up ( 32 ). In a recent study of U.S. adults, a positive correlation was found between exposure to VOCs and cardio-cerebrovascular events, including benzene, m-/p-xylene, o-xylene, and ethylbenzene ( 33 ). In addition, a study of 2011–2020 National Health Survey data found that exposure to VOCs may increase the risk of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Akkoç et al found that post-stroke patients experienced urinary urgency in about two-thirds of patients at 6month follow-up (32). In a recent study of U.S. adults, a positive correlation was found between exposure to VOCs and cardiocerebrovascular events, including benzene, m-/p-xylene, o-xylene, and ethylbenzene (33). In addition, a study of 2011-2020 National Health Survey data found that exposure to VOCs may increase the risk of depression.…”
Section: Figurementioning
confidence: 99%